A new genus and species of Ephydridae (Diptera) from the Oriental Region - Zhang, Junhua; Yang, Ding; Mathis, Wayne N. (Zootaxa, 2005)
A new genus and species of the tribe Dagini (subfamily Ephydrinae), Sinops sichuanensis, are described from specimens collected in China (Sichuan: Emeishan Mountain), and three species formerly comprising “the fluvialis group” of Psilephydra Hendel are transferred to the new genus (S. fluvialis (Miyagi), S. kaskiensis (Mathis) and S. nepalensis (Mathis)) as new combinations. A cladistic analysis of the new genus with related genera in the tribe Dagini is presented and discussed, and keys to the genera of Dagini and to the species of the new genus are presented.